Uso de implantes com hormônio liberador de gonadotrofina em fêmeas e avaliação do sêmen durante a estação reprodutiva de pacu (Piaractus mesopotamicus) - Kuradomi, Rafael Yutaka [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The aim of this study was to evaluate the possibility of ovarian maturation synchronization in a breeding herd of pacu (Piaractus mesopotamicus) by using slow-release implants with salmon gonadotropin releasing hormone analogue (sGnRHa). Furthermore, in addition of female's study, we evaluated the seminal characteristics throughout of the breeding season and the possibility of restripping. In this regard, females were implanted with sGnRHa pellets, and males were spermiated during of the breeding season and restripping were performed in males spermiated at the beginning and spermiated again at the middle of the season. To help in understanding the results, temporal variations between experimental groups of growth hormone (gh), luteinizing hormone beta subunit (lhb) and follicle-stimulating hormone beta subunit (fshb) gene expressions, and gonadal steroids concentrations were determined in males and females. In females, 35 days after pellets implantation (during the spawning period) the gene expression of lhb and fshb were increased in the treated and inhibited in the controls group, respectively, suggesting an lhb inducing effect by implant. In males, released milt volume increased throughout the breeding season, however, the indices related to sperm quality, especially to the DNA quality, were lower in the end than beginning of the season. The expressions of lhb, and gh were increased for the end season group against the reespermiado group, suggesting an association between gene expression and the maturation stage of the testes. Furthermore, the substantial increases of 11-ketotestosterone after hormonal induction in the beginning and restriping group correlated with good semen quality. We conclude that the using of implants may increases the frequency of the apt females in the spawning season. The using of semen at the end of the breeding season should be avoided and restripping is an alternative ...

O objetivo deste trabalho foi avaliar a possibilidade de induzir a sincronização da maturação ovariana em um plantel de matrizes de pacu (Piaractus mesopotamicus) por meio de uso de implantes com análogo do hormônio liberador de gonadotrofinas do salmão (sGnRHa). Além disso, complementarmente ao estudo com as fêmeas, avaliamos as características seminais dos reprodutores ao longo do ciclo reprodutivo e a possibilidade de reespermiação. Para tal, implantes de sGnRHa foram utilizados em fêmeas, reprodutores foram espermiados ao longo da estação reprodutiva e a reespermiação foi realizada em machos espermiados no inicio e novamente no meio da estação. Variações temporais e entre grupos experimentais na expressão gênica do hormônio do crescimento (gh) e subunidade beta do hormônio luteinizante (lhb) e do folículo estimulante (fshb), bem como as concentrações plasmáticas de esteroides gonadais foram determinadas em machos e fêmeas e utilizadas como ferramentas auxiliares na interpretação dos resultados. Nas fêmeas, aos 35 dias após a introdução do implante (durante o período de desova) as expressões gênicas da lhb e do fshb estavam aumentadas nas tratadas e inibidas nas controles, respectivamente, sugerindo um efeito indutor do lhb pelo implante. Nos machos, o volume de sêmen liberado aumentou ao longo do período reprodutivo, no entanto, os índices relacionados com a qualidade dos espermatozoides, principalmente a qualidade do DNA, que decresceu do começo para o término da estação. A expressão do lhb e gh estavam aumentadas no grupo do final da estação em relação ao grupo reespermiado, sugerindo uma associação entre a expressão gênica e o estádio de maturação dos testículos. Além disso, elevações substanciais de 11-cetotestosterona durante a indução hormonal, no início da estação reprodutiva e nos animais reespermiados...
Keywords: Peixe - Reprodução; Pacu (Peixe); Sêmen; Hormônio liberador de gonadotropina; Ovarios; Fishes